PENERAPAN PERATURAN SEKOLAH OLEH PESERTA DIDIK (Studi pada Kelas X dan XI di SMA PGRI 3 Padang ) - Daely, Fitriani - (Bimbingan dan Konseling, 2014)
This research is motivated by a decline in the level of discipline of students against school rules in accordance with the phenomenon in the field of students out during hours of lessons, come late to school, unplug the clock when the lesson. This research aimed to describe: (1) description of the application of school rules on standard benchmark or common properties (2) description of the application of school rules in the benchmark or standard for a particular activity. This research is descriptive quantitative research population in this research were all students of Grade XI and XII at SMA PGRI 3 Padang academic year 2013/2014 which amounted 102 people, and samples were taken by using simple random sampling technique which amounted 50 people. The research instrument was a questionnaire, to analysis data by using techniques percentage. The findings result of the research: (1) The application of school rules in the benchmark or standard of general nature indicate that learners are applied fairly, (2 The application of school rules on benchmarks or standards for specific activities by learners fairly applied. From the result of research, then the school can make correction of the weaknesses of the school system to be updated by the school, the principal can evaluate the implementation of the rules through a meeting of the school community in order to create better discipline.